2017
DOI: 10.1038/srep44329
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of social buffering of fear in zebrafish

Abstract: Some humans thrive whereas others resign when exposed to threatening situations throughout life. Social support has been identified as an important modulator of these discrepancies in human behaviour, and other social animals also exhibit phenomena in which individuals recover better from aversive events when conspecifics are present – aka social buffering. Here we studied social buffering in zebrafish, by exposing focal fish to an aversive stimulus (alarm substance – AS) either in the absence or presence of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
116
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 74 publications
8
116
1
Order By: Relevance
“…After showing that zebrafish decreased their fear response to alarm substance (AS, a known fear-inducing stimulus in this species) when in the joint presence of olfactory (shoal water) and visual (sight of shoal) cues of conspecifics, we exposed zebrafish to AS in the presence of olfactory or visual social cues separately. Our results showed that although both sensory modalities were equally effective in the short term, the visual cue was more effective in decreasing fear responses toward AS in a long-lasting exposure 8 . These differences may reflect the fact that olfactory and visual cues are refreshed at different rates in the environment, with olfactory information remaining invariable in the water for longer periods of time, hence limiting the rate at which it can be updated 8 .…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…After showing that zebrafish decreased their fear response to alarm substance (AS, a known fear-inducing stimulus in this species) when in the joint presence of olfactory (shoal water) and visual (sight of shoal) cues of conspecifics, we exposed zebrafish to AS in the presence of olfactory or visual social cues separately. Our results showed that although both sensory modalities were equally effective in the short term, the visual cue was more effective in decreasing fear responses toward AS in a long-lasting exposure 8 . These differences may reflect the fact that olfactory and visual cues are refreshed at different rates in the environment, with olfactory information remaining invariable in the water for longer periods of time, hence limiting the rate at which it can be updated 8 .…”
mentioning
confidence: 69%
“…In our study we investigated the mechanisms of social buffering of fear in zebrafish ( Danio rerio ) 8 . First, we assessed the influence of different sensory modalities to the same buffering episode and respective effectiveness in a long-lasting exposure to threat.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CAS was not able to increase antipredator responses to a sympatric predator (although the predator was not in the same tank as the receiver) in D. rerio (Speedie & Gerlai, ), although CAS increased survival of P. promelas placed in an experimental tank with a predator (Mathis & Smith, ). Moreover, D. rerio given visual and olfactory access to conspecifics show less freezing when exposed to CAS (Faustino et al ., ), an effect that has been termed social buffering. This observation, as well as the fact that D. rerio tested in groups are less likely to freeze, suggest that conspecific communication is the main function of CAS.…”
Section: Adaptive and Evolutionary Issues For Alarm Signalsmentioning
confidence: 99%
“…Interestingly, as reported above, this work also found increased cfos in the Dm, Vv, and 188 POA. Importantly, control animals showed functional connectivity between these regions, while 189 exposure to CAS decreased these correlations; in fact, animals exposed to CAS showed only co-190 activation of Dm-Vs and Vv-Vs (Faustino et al, 2017). The precise mechanism for this decreased 191…”
Section: /44mentioning
confidence: 99%